Concomitant initiation of radical and cationic polymerisations using new copper complexes as photoinitiators: Synthesis and characterisation of acrylate/epoxy interpenetrated polymer networks. (5th June 2021) - Mau, Alexandre; Dietlin, Céline; Dumur, Frédéric; Lalevée, Jacques
Graphical abstract: Highlights: Two new copper complexes were investigated for both radical and cationic polymerisation under air. The formations of acrylate/epoxy interpenetrated polymer networks were successfully performed. Several characterisations of the interpenetrated polymer networks were done. The advantages of IPNs are highlighted. Abstract: Two new copper complexes were investigated in three-component visible light photoinitiating system for both radical and cationic polymerisation under air. Their reactivity and efficiency have been compared with that of a highly efficient photoredox catalyst. The formation of acrylate/epoxy interpenetrated polymer networks were successfully performed through concomitant initiation of radical and cationic polymerisation with low copper complex content upon either LED@405 nm or LED@455 nm irradiations. Several characterisations of the acrylate/epoxy IPNs final properties, such as the mechanical properties, adhesion properties, shrinkage and swelling, indicated the possibilities to adapt or tune their properties compared to radical polymerisation of TMPTA.